Positive electrode, electrochemical device including the same, and electronic device
Patent Information
- Application Number
- JP2024210505
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-10-19
Smart Images

Figure 2025032185000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of energy storage, in particular to cathode materials and electrochemical devices containing same, and electronic devices, especially high energy density secondary lithium batteries. [Background technology]
[0002] With the development of the lithium-ion battery industry, the market is also increasing its requirements for the dynamic performance and energy density of lithium-ion batteries. The difference in the conductive ability of the positive electrode material and the high electronic resistance make the battery resistance a little high. At the same time, the high compression density of the positive electrode causes the problem of brittle fracture when folded in half. There is an urgent need in the market for a new lithium-ion battery to solve this technical problem. Summary of the Invention
[0003] The present invention provides a positive electrode that is intended to solve, at least to some extent, at least one problem existing in the related art. The present invention also provides electrochemical and electronic devices that use the positive electrode.
[0004] In one embodiment, the present invention provides a positive electrode comprising: a current collector; and a positive electrode active material layer located on the current collector, the positive electrode active material layer comprising a positive electrode active material and graphene, and a ratio Dv50 / D1 of a particle diameter Dv50 of the positive electrode active material to a sheet diameter D1 of the graphene is 0.45 to 4.5.
[0005] In some embodiments, the ratio Dv10 / Dv50 of the particle diameters Dv10 and Dv50 of the positive electrode active material is 0.25 to 0.5.
[0006] In some embodiments, the positive electrode active material has a particle size Dv50 of 0.5 μm to 35 μm.
[0007] In some embodiments, the number of graphene layers is n, where n is 1-30, preferably 7-20.
[0008] In some embodiments, the positive electrode active material layer further comprises a particulate conductive agent, and a particle diameter D2 of the particulate conductive agent and a particle diameter Dv50 of the positive electrode active material satisfy D2 / Dv50<0.4.
[0009] In some embodiments, the particulate conductive agent comprises at least one of conductive carbon black, Super P, acetylene black, Ketjen black, and graphite.
[0010] In some embodiments, the ratio Dv99 / D1 of the particle diameter Dv99 of the positive electrode active material to the sheet diameter D1 of the graphene is 3.2 to 4.6.
[0011] In some embodiments, the positive electrode active material layer has a sheet resistance of 0.1 ohm to 550 ohm.
[0012] In some embodiments, the positive electrode active material layer has a compressed density of 3.5 g / cc to 4.5 g / cc.
[0013] In some embodiments, the positive electrode active material includes at least one of a lithium transition metal composite oxide and a lithium-containing transition metal phosphate compound.
[0014] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate.
[0015] In some embodiments, the graphene content is 0.1 wt.% to 5 wt.%, based on the total weight of the positive electrode active material layer.
[0016] In some embodiments, the coating area density of the positive electrode active material layer is 200 mg / 1540.25 mm 2~330mg / 1540.25mm 2 It is.
[0017] In another embodiment, the present invention provides an electrochemical device comprising a positive electrode according to any embodiment of the present invention.
[0018] In another embodiment, the present invention provides an electronic device comprising an electrochemical device according to any embodiment of the present invention.
[0019] The positive electrode provided by the present invention has a reduced electronic resistance and improved flexibility, and can improve the problem of brittle fracture of the positive electrode at high compression density.
[0020] Other aspects and advantages of embodiments of the invention will be set forth in the following description, in part, and / or may be learned by the practice of the embodiments of the invention. [Brief description of the drawings]
[0021] In the following, in order to more easily explain the embodiments of the present invention, drawings necessary for explaining the embodiments of the present invention and the prior art will be briefly described. Obviously, the drawings described below only show a part of the embodiments of the present invention. Those skilled in the art can still obtain drawings of other embodiments according to the configurations illustrated in these drawings. [Figure 1] FIG. 1 shows a scanning electron microscope (SEM) photograph of a positive electrode in Example 3 according to the present invention, and the straight lines in the figure indicate the diameters of graphene sheets. [Diagram 2] FIG. 2 is an SEM photograph of the positive electrode in Example 18 according to the present invention, which shows that graphene is present around the positive electrode active material particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The embodiments of the present invention are described in detail below, but it should be understood that the embodiments of the present invention are not intended to limit the scope of the present invention.
[0023] As used herein, amounts, ratios, and other numerical values are expressed in a range format, with the understanding that such range format is used for convenience and brevity, and should be understood to be flexible and include not only the numerical values explicitly specified as range limits, but also all individual numerical values or subranges contained within the range, so long as each numerical value and subrange is explicitly specified.
[0024] In specific embodiments and claims, a list of terms connected with the terms "one of," "one of," "a type of," or other similar terms means any one of the listed terms. For example, if term A and term B are listed, the short phrase "one of A and B" means only A or only B. In another example, if term A, term B, and term C are listed, the short phrase "one of A, B, and C" means only A, only B, or only C. Term A may include a single element or multiple elements. Term B may include a single element or multiple elements. Term C may include a single element or multiple elements.
[0025] In specific embodiments and claims, a list of terms connected with the terms "at least one of," "at least one of," "at least one of," or other similar terms means any combination of the listed terms. For example, if term A and term B are listed, the short phrase "one of A and B" means only A or only B. In another example, if term A, term B, and term C are listed, the short phrase "one of A, B, and C" means only A, only B, or only C. Term A may include a single element or multiple elements. Term B may include a single element or multiple elements. Term C may include a single element or multiple elements.
[0026] In one embodiment, the present invention provides an electrochemical device including a positive electrode, a negative electrode, a separator, and an electrolyte. I, positive electrode
[0027] In some embodiments, the present invention provides a positive electrode comprising: a current collector; and a positive electrode active material layer located on the current collector, the positive electrode active material layer comprising a positive electrode active material and graphene, wherein a ratio Dv50 / D1 of a particle diameter Dv50 of the positive electrode active material to a sheet diameter D1 of the graphene is 0.45 to 4.5.
[0028] In some embodiments, the positive electrode active material layer is located on one surface of the current collector, hi some embodiments, the positive electrode active material layer is located on both surfaces of the current collector.
[0029] In some embodiments, Dv50 / D1 is 0.45, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, 2.8, 3.0, 3.2, 3.5, 3.7, 4.0, 4.2, 4.5, or any combination thereof within these ranges. In some embodiments, Dv50 / D1 is preferably between 1.0 and 3.5.
[0030] In some embodiments, the ratio Dv10 / Dv50 of the particle diameter Dv10 to Dv50 of the positive electrode active material is 0.25 to 0.5. In some embodiments, Dv10 / Dv50 is 0.25, 0.27, 0.30, 0.32, 0.35, 0.38, 0.40, 0.42, 0.45, 0.48, 0.5, or any range of values therebetween. In some embodiments, Dv10 / Dv50 is preferably 0.33 to 0.45.
[0031] In some embodiments, the particle size Dv50 of the positive electrode active material is 0.5 μm to 35 μm. In some embodiments, the particle size Dv50 of the positive electrode active material is 0.5 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, or any value within the above range. In some embodiments, Dv50 is preferably 10 μm to 25 μm.
[0032] In some embodiments, the number of graphene layers is n, and n is between 1 and 30. In some embodiments, n is between 1, 3, 5, 10, 12, 15, 18, 20, 23, 25, 28, 30, or any range between these values. In some embodiments, n is preferably between 7 and 20.
[0033] In some embodiments, the positive electrode active material layer further comprises a particulate conductive agent, and a particle diameter D2 of the particulate conductive agent and a particle diameter Dv50 of the positive electrode active material satisfy D2 / Dv50<0.4.
[0034] In some embodiments, D2 / Dv50 is 0.02, 0.04, 0.06, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.23, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, or any combination thereof within these ranges. In some embodiments, D2 / Dv50 is preferably between 0.04 and 0.25.
[0035] In some embodiments, the particulate conductive agent comprises at least one of conductive carbon black, Super P, acetylene black, Ketjen black, and graphite.
[0036] In some embodiments, the ratio Dv99 / D1 of the particle diameter Dv99 of the positive electrode active material to the sheet diameter D1 of the graphene is 3.2 to 4.6.
[0037] In some embodiments, Dv99 / D1 is 3.2, 3.5, 3.8, 4.0, 4.2, 4.4, 4.6, or a range consisting of any and both of these values.
[0038] In some embodiments, the sheet resistance of the positive electrode active material layer is 0.1 ohm to 550 ohm. In some embodiments, the sheet resistance of the positive electrode active material layer is 0.1 ohm, 1 ohm, 3 ohm, 6 ohm, 8 ohm, 10 ohm, 30 ohm, 60 ohm, 90 ohm, 110 ohm, 120 ohm, 150 ohm, 180 ohm, 200 ohm, 220 ohm, 250 ohm, 280 ohm, 300 ohm, 320 ohm, 350 ohm, 380 ohm, 400 ohm, 420 ohm, 450 ohm, 480 ohm, 500 ohm, 530 ohm, 550 ohm, or any range of values therebetween. In some embodiments, the sheet resistance of the positive electrode active material layer is preferably 0.1 to 10 ohm.
[0039] In some embodiments, the compressed density of the positive electrode active material layer is 3.5 g / cc to 4.5 g / cc. In some embodiments, the compressed density of the positive electrode active material layer is 3.5 g / cc, 3.7 g / cc, 3.9 g / cc, 4.0 g / cc, 4.2 g / cc, 4.4 g / cc, 4.5 g / cc, or any value within the range. In some embodiments, the compressed density of the positive electrode active material layer is preferably 4.0 g / cc to 4.5 g / cc.
[0040] In the present invention, the compressed density and the limit compressed density of the positive electrode active material layer are defined as follows: compressed density of the positive electrode active material layer = mass of the positive electrode active material layer per unit area (g / cm 2 The mass of the positive electrode active material layer per unit area can be weighed using a balance, and the thickness of the positive electrode active material layer can be measured using a micrometer.
[0041] The limit compression density of the positive electrode active material layer means the compression density of the positive electrode active material layer when the positive electrode is subjected to the maximum compression amount.
[0042] In some embodiments, the positive electrode active material includes at least one of a lithium transition metal composite oxide and a lithium-containing transition metal phosphate compound.
[0043] In some embodiments, the positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate.
[0044] In some embodiments, the graphene content is 0.1 wt.% to 5 wt.% based on the total weight of the positive electrode active material layer. In some embodiments, the graphene content is 0.1 wt.%, 0.6 wt.%, 1 wt.%, 1.2 wt.%, 1.5 wt.%, 1.8 wt.%, 2.0 wt.%, 2.2 wt.%, 2.5 wt.%, 2.8 wt.%, 3.0 wt.%, 3.2 wt.%, 3.5 wt.%, 3.8 wt.%, 4.0 wt.%, 4.2 wt.%, 4.5 wt.%, 4.8 wt.%, 5 wt.%, or any range of both of these values based on the total weight of the positive electrode active material layer. In some embodiments, the graphene content is preferably 0.2 wt.% to 1.00 wt.%.
[0045] In some embodiments, the coating area density of the positive electrode active material layer is 200 mg / 1540.25 mm 2 ~330mg / 1540.25mm 2 In some embodiments, the coating surface density C of the positive electrode active material layer is 200 mg / 1540.25 mm 2 , 230mg / 1540.25mm 2 , 260mg / 1540.25mm 2 , 280mg / 1540.25mm 2 , 300mg / 1540.25mm 2 , 330mg / 1540.25mm 2 or any range consisting of both of these values.
[0046] In some embodiments, the positive electrode active material layer may be one or more layers, such as two, three, four, five layers, or a range of any and all of these values. In some embodiments, each layer in a multiple layer positive electrode active material layer may include the same or different positive electrode active materials.
[0047] An electrode (positive or negative electrode) of an electrochemical device (e.g., a lithium ion battery) is generally prepared by mixing an active material, a conductive agent, a thickener, a binder, and a solvent, and applying the mixed slurry to a current collector. The theoretical capacity of an electrochemical device varies depending on the type of active material. In general, an electrochemical device suffers from a phenomenon that the charge / discharge capacity decreases with the progress of cycles. This is because the electrode active material cannot perform its function due to changes in the electrode interface during charging and / or discharging.
[0048] The inventors of the present invention unexpectedly discovered the following: By controlling the ratio Dv50 / D1 of the Dv50 of the positive electrode active material to the sheet diameter D1 of the graphene within a predetermined range, the electronic resistance of the positive electrode can be improved and the flexibility of the positive electrode can be improved, thereby avoiding the problem of brittle fracture of the positive electrode when the compression density is high. (1) Positive electrode active material
[0049] The type of the positive electrode active material in the present invention is not particularly limited, and may be any material capable of electrochemically absorbing and releasing metal ions (e.g., lithium ions). In some embodiments, the positive electrode active material is a material containing lithium and at least one transition metal. In some embodiments, the positive electrode active material may include, but is not limited to, for example, lithium transition metal composite oxide and lithium-containing transition metal phosphate compound.
[0050] In some embodiments, the transition metal in the lithium transition metal composite oxide includes V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium transition metal composite oxide includes lithium cobalt composite oxide such as LiCoO2, lithium nickel composite oxide such as LiNiO2, lithium manganese composite oxide such as LiMnO2, LiMn2O4, Li2MnO4, LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2, LiNi 0.5 Mn 0.3 Co 0.2 Lithium transition metal composite oxides include lithium nickel manganese cobalt composite oxides such as O2. In these, some of the transition metal atoms that are the main components of these lithium transition metal composite oxides are replaced with other elements such as Na, K, B, F, Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Nb, Mo, Sn, and W. Examples of lithium transition metal composite oxides include LiNi 0.5 Mn 0.5 O2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.45 Co 0.10 Al 0.45 O2, LiMn 1.8 Al 0.2 O4 and LiMn 1.5 Ni 0.5 Examples of combinations of lithium transition metal composite oxides include, but are not limited to, combinations of LiCoO2 and LiMn2O4, but are not limited thereto. A part of Mn in LiMn2O4 may be replaced with a transition metal (e.g., LiNi 0.33 Co 0.33 Mn 0.33 O2), a part of the Co in LiCoO2 may be substituted with a transition metal.
[0051] In some embodiments, the transition metals in the lithium-containing transition metal phosphate compound include V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc. In some embodiments, the lithium-containing transition metal phosphate compounds include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, and cobalt phosphates such as LiCoPO4. However, some of the transition metal atoms that are the main components of these lithium transition metal phosphate compounds are substituted with other elements such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Nb, Si, etc.
[0052] In some embodiments, using the powdery material of lithium transition metal oxide Li a M b O2, 0.9 < a < 1.1 and 0.9 < b < 1.1, where M is a transition metal mainly selected from Mn, Co, and Ni, and the composition M varies according to the particle size.
[0053] In some embodiments, in the powdery electrode active material of lithium transition metal oxide Li a M b O2, M = A Z A' Z' M' 1-Z-Z' where M' = Mn x Ni y Co 1-x-y 0 ≤ y ≤ 1, 0 ≤ x ≤ 1, 0 ≤ Z + Z' < 0.1, Z' < 0.02, A is at least one selected from the elements Al, Mg, Ti, Cr, and A' is at least one selected from the elements F, Cl, S, Zr, Ba, Y, Ca, B, Be, Sn, Sb, Na, Zn.
[0054] In some embodiments, the average composition of the transition metal is M = Mn x Ni y Co 1-x-y and 0.03 < x < 0.35.
[0055] In some embodiments, the average composition of the transition metal is M = Mn x Ni y Co 1-x-yand 0.03 <xであり、x+y<0.7である。
[0056] In some embodiments, the composition is related to size. a M b In the powdered electrode active material containing O2, basically all parts of the whole particle have a layered crystal structure, and the larger particles are Li a M b O2, M=Mn x Ni y Co 1-x-y , x+y<0.35, and the small particles are Li a M b O2, M=Mn x' Ni y' Co 1-x'-y' and the small particles have lower Co, at least 10%, (1-x'-y')<0.9×(1-xy), and higher Mn, at least 5%, x'-x>0.05. This allows for a powder with a composition related to size. That is, a component with larger particles (e.g., distribution centered at ≧20 μm) can diffuse in the bulk phase at a faster rate. Another component has smaller particles (e.g., distribution around 5 μm), and the component can be made safe. This provides an electrode active material with high cycle stability and high safety, as well as high volumetric energy density and high gravimetric energy density.
[0057] In some embodiments, the single particles are essentially lithium transition metal oxides with Co content that continuously increases with particle size.
[0058] In some embodiments, the single particles further contain Mn in the transition metals, and the Mn content decreases continuously with particle size.
[0059] In some embodiments, the large particles have a composition close to LiCoO2, which allows for a high Li diffusion constant, and therefore sufficient rate performance. The large particles occupy only a small portion of the total surface area of the cathode, which limits the amount of heat released by reacting with the electrolyte on the surface or outer portion, resulting in less large particles and therefore poor safety. The small particles have a composition containing less Co, which allows for improved safety. The low lithium diffusion constant is tolerated by the small particles due to the short solid diffusion path length, without significant loss of rate performance.
[0060] In some embodiments, the preferred composition of the small particles contains less Co and more stable elements, such as Mn, allowing slower Li diffusion in the bulk, but with higher surface stability. In the negative electrode active material powder of the present invention, the preferred composition of the large particles contains more Co and less Mn, since it requires faster Li diffusion in the bulk, but allows for slightly lower surface stability.
[0061] In some embodiments, the composition is Li x Within a single particle that is MO2, preferably at least 80 w% of M is cobalt or nickel. In some embodiments, the inner portion of the particle has a composition close to LiCoO2. The outer portion is lithium manganese nickel cobalt oxide.
[0062] A powdered electrode active material whose composition is related to size can be made by depositing a precipitate containing at least one transition metal onto a seed particle having a different transition metal composition than the precipitate, adding a quantity of a lithium source, and performing at least one heat treatment such that essentially all of the resulting particles contain a core derived from the seed, which core is completely covered by a layer of precipitate. (2) Positive electrode current collector
[0063] The type of the positive electrode current collector is not particularly limited and may be any known material suitable for a positive electrode current collector. Examples of the positive electrode current collector may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating layer, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0064] The shape of the positive electrode current collector is not particularly limited. When the positive electrode current collector is a metal material, the shape of the positive electrode current collector may include, but is not limited to, a metal foil, a metal cylinder, a metal coil, a metal plate, a metal film, a metal plate mesh, a stamping metal, a metal foam, and the like. When the positive electrode current collector is a carbon material, the shape of the positive electrode current collector may include, but is not limited to, a carbon plate, a carbon film, a carbon cylinder, and the like. In some embodiments, the positive electrode current collector is a metal film. In some embodiments, the metal film is in the form of a mesh. The thickness of the metal film is not particularly limited. In some embodiments, the thickness of the metal film is greater than 1 μm, greater than 3 μm, or greater than 5 μm. In some embodiments, the thickness of the metal film is less than 1 mm, less than 100 μm, or less than 50 μm. In some embodiments, the thickness of the metal film is within the range consisting of any two of the above values.
[0065] In order to reduce the electronic contact resistance between the positive electrode collector and the positive electrode active material layer, a conductive additive may be included on the surface of the positive electrode collector. Examples of the conductive additive may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver.
[0066] The thickness ratio of the positive electrode collector to the positive electrode active material layer is the ratio of the thickness of the positive electrode active material layer on one side before the electrolyte is injected to the thickness of the positive electrode collector, and the value is not particularly limited. In some embodiments, the thickness ratio of the positive electrode collector to the positive electrode active material layer is less than 20, less than 15, or less than 10. In some embodiments, the thickness ratio of the positive electrode collector to the positive electrode active material layer is greater than 0.5, greater than 0.8, or greater than 1. In some embodiments, the thickness ratio of the positive electrode collector to the positive electrode active material layer is within a range consisting of any two of the above values. When the thickness ratio of the positive electrode collector to the positive electrode active material layer is within the above range, the heat dissipation of the positive electrode collector during charging and discharging at a high current density can be suppressed, and the capacity of the electrochemical device can be ensured. II, negative electrode
[0067] The negative electrode includes a negative electrode current collector and a negative electrode active material layer located on one or both sides of the negative electrode current collector. Negative electrode active material layer
[0068] The negative electrode active material layer includes a negative electrode active material. The negative electrode active material layer may be one or more layers, and each layer in the multiple layers of the negative electrode active material layer may include the same or different negative electrode active materials. The negative electrode active material is any material that can reversibly absorb and release metal ions, such as lithium ions. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent unintentional deposition of lithium metal on the negative electrode during charging. (1) Carbon materials
[0069] In some embodiments, the negative electrode active material layer comprises a carbon material.
[0070] In some embodiments, the negative electrode active material layer includes at least one of artificial graphite, natural graphite, mesocarbon microbeads, soft carbon, hard carbon, and amorphous carbon.
[0071] In some embodiments, the surface of the carbonaceous material comprises amorphous carbon.
[0072] In some embodiments, the shape of the carbonaceous material may include, but is not limited to, fibers, spheres, particles, and flakes.
[0073] In some embodiments, the carbon material has at least one of the following characteristics: (a) 5m 2 / g specific surface area (BET), and (b) Median diameter (Dv50) from 5 μm to 30 μm. Specific surface area (BET)
[0074] In some embodiments, the carbon material is 5 mm 2 In some embodiments, the carbon material has a specific surface area of less than 3 m 2 In some embodiments, the carbon material has a specific surface area of less than 1 m 2 In some embodiments, the carbon material has a specific surface area of less than 0.1 m 2 In some embodiments, the carbon material has a specific surface area of more than 0.7 m 2 In some embodiments, the carbon material has a specific surface area of less than 0.5 m 2 / g. In some embodiments, the specific surface area of the carbon material is within the range of any two of the above values. When the specific surface area of the carbon material is within the above range, lithium deposition on the surface of the electrode can be suppressed, and gas generation due to a reaction between the negative electrode and the electrolyte can be suppressed.
[0075] The porosity of the negative electrode active material layer can be measured using a density measuring device AccuPyc II 1340, with each sample being measured at least three times, and the average value of the at least three data is taken to calculate the porosity of the negative electrode active material layer according to the following formula: Porosity=(V1-V2) / V1×100%, where V1 is the apparent volume, V1=surface area of sample×thickness of sample×number of samples, and V2 is the true volume. Median diameter (Dv50)
[0076] The median diameter (Dv50) of the carbon material means the volume-based average particle diameter obtained by a laser diffraction / scattering method. In some embodiments, the median diameter (Dv50) of the carbon material is 5 μm to 30 μm. In some embodiments, the median diameter (Dv50) of the carbon material is 10 μm to 25 μm. In some embodiments, the median diameter (Dv50) of the carbon material is 15 μm to 20 μm. In some embodiments, the median diameter (Dv50) of the carbon material is 1 μm, 3 μm, 5 μm, 7 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, or a range consisting of any of both of these values. When the median diameter of the carbon material is within the above range, the irreversible capacity of the electrochemical device is small, and the negative electrode is easily applied uniformly.
[0077] The median diameter (Dv50) of the carbon material can be measured by dispersing the carbon material in a 0.2 wt % aqueous solution (10 mL) of polyoxyethylene (20) sorbitan monolaurate and using a laser diffraction / scattering particle size distribution analyzer (LA-700 manufactured by Horiba, Ltd.). (2) (Other ingredients) Materials containing silicon and / or tin elements
[0078] In some embodiments, the anode active material layer further comprises at least one of a silicon-containing material, a tin-containing material, and an alloy material. In some embodiments, the anode active material layer further comprises at least one of a silicon-containing material and a tin-containing material. In some embodiments, the anode active material layer further comprises one or more of a silicon-containing material, a silicon carbon composite material, a silicon oxide material, an alloy material, and a lithium-containing metal composite oxide material. In some embodiments, the anode active material layer further comprises other types of anode active materials, such as one or more materials containing metal elements and metalloid elements that can form an alloy with lithium. In some embodiments, examples of the metal elements and metalloid elements may include, but are not limited to, Mg, B, Al, Ga, In, Si, Ge, Sn, Pb, Bi, Cd, Ag, Zn, Hf, Zr, Y, Pd, and Pt. In some embodiments, examples of the metal elements and metalloid elements include Si, Sn, or combinations thereof. Si and Sn have excellent lithium ion release capabilities, and therefore can provide high energy density to lithium ion batteries. In some embodiments, the other types of negative electrode active materials may further include one or more of metal oxides and polymer compounds. In some embodiments, the metal oxides may include, but are not limited to, iron oxide, ruthenium oxide, and molybdenum oxide. In some embodiments, the polymer compounds may include, but are not limited to, polyacetylene, polyaniline, and polypyrrole. Negative electrode conductive material
[0079] In some embodiments, the negative electrode active material layer further includes a negative electrode conductive material, which may include any conductive material as long as it does not cause a chemical change. Non-limiting examples of the conductive material include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof. Negative electrode binder
[0080] In some embodiments, the negative electrode active material layer further includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of the negative electrode binder is not particularly limited as long as it is a material that is stable in the electrolyte or the solvent used in preparing the electrode.
[0081] Examples of negative electrode binders include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, polyimide, cellulose, and nitrocellulose; rubber-like polymers such as styrene-butadiene rubber (SBR), isoprene rubber, polybutadiene rubber, fluororubber, acrylonitrile-butadiene rubber (NBR), and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or hydrogenated products thereof; ethylene-propylene-diene terpolymers (EPDM), and styrene-ethylene-butadiene-styrene copolymers. The negative electrode binder may include, but is not limited to, thermoplastic elastomeric polymers such as styrene-isoprene-styrene block copolymers or hydrogenated products thereof, soft resinous polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; and polymer compositions having ion conductivity for alkali metal ions (e.g., lithium ions). The negative electrode binder may be used alone or in any combination.
[0082] In some embodiments, the content of the negative electrode binder is greater than 0.1 wt%, greater than 0.5 wt%, or greater than 0.6 wt%, based on the total weight of the negative electrode active material layer. In some embodiments, the content of the negative electrode binder is less than 20 wt%, less than 15 wt%, less than 10 wt%, or less than 8 wt%, based on the total weight of the negative electrode active material layer. In some embodiments, the content of the negative electrode binder is within a range consisting of any two of the above values. When the content of the negative electrode binder is within the above range, the capacity of the electrochemical device and the strength of the negative electrode can be sufficiently ensured.
[0083] When the anode active material layer includes a rubbery polymer (e.g., SBR), in some embodiments, the anode binder content is greater than 0.1 wt%, greater than 0.5 wt%, or greater than 0.6 wt%, based on the total weight of the anode active material layer. In some embodiments, the anode binder content is less than 5 wt%, less than 3 wt%, or less than 2 wt%, based on the total weight of the anode active material layer. In some embodiments, the anode binder content is within the range consisting of any two of the above values, based on the total weight of the anode active material layer.
[0084] When the anode active material layer includes a fluorine-based polymer (e.g., polyvinylidene fluoride), in some embodiments, the content of the anode binder is greater than 1 wt%, greater than 2 wt%, or greater than 3 wt%, based on the total weight of the anode active material layer. In some embodiments, the content of the anode binder is less than 15 wt%, less than 10 wt%, or less than 8 wt%, based on the total weight of the anode active material layer. Based on the total weight of the anode active material layer, the content of the anode binder is within the range consisting of any two of the above values. solvent
[0085] The type of solvent for forming the negative electrode slurry is not particularly limited as long as it can dissolve or disperse the negative electrode active material, the negative electrode binder, and, if necessary, the thickener and the conductive material. In some embodiments, the solvent for forming the negative electrode slurry can be any one of an aqueous solvent and an organic solvent. Examples of the aqueous solvent include, but are not limited to, water, alcohol, and the like. Examples of the organic solvent include, but are not limited to, N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethylenetriamine, N,N-dimethylaminopropylamine, tetrahydrofuran (THF), toluene, acetone, diethyl ether, hexamethylphosphoramide, dimethylsulfoxide, benzene, xylene, quinoline, pyridine, methylnaphthalene, hexane, and the like. The solvents can be used alone or in any combination. Thickener
[0086] The thickener is generally used to adjust the viscosity of the negative electrode slurry. The type of the thickener is not limited, and examples thereof may include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof. The thickener may be used alone or in any combination.
[0087] In some embodiments, the content of the thickener is more than 0.1 wt%, more than 0.5 wt%, or more than 0.6 wt%, based on the total weight of the negative electrode active material layer. In some embodiments, the content of the thickener is less than 5 wt%, less than 3 wt%, or less than 2 wt%, based on the total weight of the negative electrode active material layer. When the content of the thickener is within the above range, the capacity decrease and the resistance increase of the electrochemical device can be suppressed, and the negative electrode slurry can have good coating properties. Surface Coating
[0088] In some embodiments, a material different from the composition of the negative electrode active material layer can be attached to the surface of the negative electrode active material layer. Examples of the material attached to the surface of the negative electrode active material layer may include, but are not limited to, oxides such as aluminum oxide, silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate. (3) Content of negative electrode active material
[0089] In some embodiments, the amount of anode active material is greater than 80 wt%, greater than 82 wt%, or greater than 84 wt%, based on the total weight of the anode active material layer. In some embodiments, the amount of anode active material is less than 99 wt%, or less than 98 wt%, based on the total weight of the anode active material layer. In some embodiments, the amount of anode active material is within the range consisting of any two of the above numbers, based on the total weight of the anode active material layer. (4) Thickness of the negative electrode active material layer
[0090] By thickness of the negative electrode active material layer is meant the thickness of the negative electrode active material layer on either side of the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer is greater than 15 μm, greater than 20 μm, or greater than 30 μm. In some embodiments, the thickness of the negative electrode active material layer is less than 300 μm, less than 280 μm, or less than 250 μm. In some embodiments, the thickness of the negative electrode active material layer is within the range consisting of any two of the above values. (5) Density of negative electrode active material
[0091] In some embodiments, the density of the negative electrode active material in the negative electrode active material layer is 1 g / cm 3 Super, 1.2g / cm 3 More than 1.3g / cm 3 In some embodiments, the density of the negative electrode active material in the negative electrode active material layer is greater than 2.2 g / cm 3 Less than 2.1g / cm 3Less than 2.0g / cm 3 Less than or equal to 1.9g / cm 3 In some embodiments, the density of the negative electrode active material in the negative electrode active material layer is within the range consisting of any two of the above values. When the density of the negative electrode active material is within the above range, destruction of the negative electrode active material particles can be prevented, an increase in the initial irreversible capacity of the electrochemical device or a deterioration in the high current density charge / discharge characteristics due to a decrease in the permeability of the electrolyte around the negative electrode current collector / negative electrode active material interface can be suppressed, and further a decrease in the capacity and an increase in the resistance of the electrochemical device can be suppressed. negative electrode current collector
[0092] The current collector that holds the negative electrode active material can be any current collector known in the art. Examples of the negative electrode current collector can include, but are not limited to, metal materials such as aluminum, copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.
[0093] When the negative electrode current collector is a metal material, the form of the negative electrode current collector may include, but is not limited to, a metal foil, a metal cylinder, a metal coil, a metal plate, a metal film, a metal plate mesh, a stamping metal, a metal foam, etc. In some embodiments, the negative electrode current collector is a metal film. In some embodiments, the negative electrode current collector is a copper foil. In some embodiments, the negative electrode current collector is a rolled copper foil by a rolling method or an electrolytic copper foil by an electrolytic method.
[0094] In some embodiments, the thickness of the negative electrode current collector is greater than 1 μm or greater than 5 μm. In some embodiments, the thickness of the negative electrode current collector is less than 100 μm or less than 50 μm. In some embodiments, the thickness of the negative electrode current collector is within the range consisting of any two of the above values.
[0095] The thickness ratio of the negative electrode current collector to the negative electrode active material layer is the ratio of the thickness of the negative electrode active material layer on one side to the thickness of the negative electrode current collector before the electrolyte is injected, and the value is not particularly limited. In some embodiments, the thickness ratio of the negative electrode current collector to the negative electrode active material layer is less than 150, less than 20, or less than 10. In some embodiments, the thickness ratio of the negative electrode current collector to the negative electrode active material layer is greater than 0.1, greater than 0.4, or greater than 1. In some embodiments, the thickness ratio of the negative electrode current collector to the negative electrode active material layer is within a range consisting of any two of the above values. When the thickness ratio of the negative electrode current collector to the negative electrode active material layer is within the above range, the capacity of the electrochemical device can be ensured, and heat dissipation of the negative electrode current collector during charging and discharging at a high current density can be suppressed. III, Electrolyte
[0096] The electrolytic solution used in the electrochemical device of the present invention includes an electrolyte and a solvent that dissolves the electrolyte. In some embodiments, the electrolytic solution used in the electrochemical device of the present invention further includes an additive.
[0097] In some embodiments, the electrolyte further comprises a non-aqueous solvent, which may be used as a solvent for any electrolyte solution known in the art.
[0098] In some embodiments, the non-aqueous solvent may include, but is not limited to, one or more of cyclic carbonates, chain carbonates, cyclic carboxylic acid esters, chain carboxylic acid esters, cyclic ethers, chain ethers, phosphorus-containing organic solvents, sulfur-containing organic solvents, and aromatic fluorine-containing solvents.
[0099] In some embodiments, examples of the cyclic carbonate may include, but are not limited to, one or more of ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate. In some embodiments, the cyclic carbonate has 3 to 6 carbon atoms.
[0100] In some embodiments, examples of the chain carbonate may include, but are not limited to, one or more of chain carbonates such as dimethyl carbonate, methyl ethyl carbonate, diethyl carbonate (DEC), methyl-n-propyl carbonate, ethyl-n-propyl carbonate, di-n-propyl carbonate, etc. Examples of fluorine-substituted chain carbonate may include, but are not limited to, one or more of bis(fluoromethyl)carbonate, bis(difluoromethyl)carbonate, bis(trifluoromethyl)carbonate, bis(2-fluoroethyl)carbonate, bis(2,2-difluoroethyl)carbonate, bis(2,2,2-trifluoroethyl)carbonate, 2-fluoroethylmethylcarbonate, 2,2-difluoroethylmethylcarbonate, and 2,2,2-trifluoroethylmethylcarbonate.
[0101] In some embodiments, examples of the cyclic carboxylic acid ester may include, but are not limited to, one or more of γ-butyrolactone and γ-valerolactone. In some embodiments, some hydrogen atoms of the cyclic carboxylic acid ester may be substituted with fluorine.
[0102] In some embodiments, examples of the chain carboxylic acid ester may include, but are not limited to, one or more of methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate, ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate, and ethyl pivalate. In some embodiments, some hydrogen atoms of the chain carboxylic acid ester may be substituted with fluorine. In some embodiments, examples of the fluorine-substituted chain carboxylic acid ester may include, but are not limited to, methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, butyl trifluoroacetate, and 2,2,2-trifluoroethyl trifluoroacetate.
[0103] In some embodiments, examples of the cyclic ethers may include, but are not limited to, one or more of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 2-methyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,3-dioxane, 1,4-dioxane, and dimethoxypropane.
[0104] In some embodiments, examples of the chain ether may include, but are not limited to, one or more of dimethoxymethane, 1,1-dimethoxyethane, 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2-diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane, and 1,2-ethoxymethoxyethane.
[0105] In some embodiments, examples of the phosphorus-containing organic solvent may include, but are not limited to, one or more of trimethyl phosphate, triethyl phosphate, dimethylethyl phosphate, methyldiethyl phosphate, ethylenemethyl phosphate, ethyleneethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, triphenyl phosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(2,2,3,3,3-pentafluoropropyl)phosphate, and the like.
[0106] In some embodiments, examples of the sulfur-containing organic solvent may include, but are not limited to, one or more of sulfolane, 2-methylsulfolane, 3-methylsulfolane, dimethylsulfone, diethylsulfone, ethylmethylsulfone, methylpropylsulfone, dimethylsulfoxide, methyl methanesulfonate, ethyl methanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, diethyl sulfate, and dibutyl sulfate. In some embodiments, some hydrogen atoms of the sulfur-containing organic solvent may be replaced with fluorine.
[0107] In some embodiments, the aromatic fluorine-containing solvent may include, but is not limited to, one or more of fluorobenzene, difluorobenzene, trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, and trifluoromethylbenzene.
[0108] In some embodiments, the solvent used in the electrolyte of the present invention includes cyclic carbonates, linear carbonates, cyclic carboxylic acid esters, linear carboxylic acid esters, and combinations thereof. In some embodiments, the solvent used in the electrolyte of the present invention includes at least one of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, n-propyl acetate, and ethyl acetate. In some embodiments, the solvent used in the electrolyte of the present invention includes ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof.
[0109] After adding the chain carboxylate ester and / or the cyclic carboxylate ester to the electrolyte, the chain carboxylate ester and / or the cyclic carboxylate ester form a passivation film on the surface of the electrode, thereby improving the capacity retention rate after intermittent charging cycles of the electrochemical device. In some embodiments, the electrolyte contains 1% to 60% of the chain carboxylate ester, the cyclic carboxylate ester, and combinations thereof. In some embodiments, the electrolyte contains ethyl propionate, propyl propionate, γ-butyrolactone, and combinations thereof, and the content of the combination is 1% to 60%, 10% to 60%, 10% to 50%, or 20% to 50% based on the total weight of the electrolyte. In some embodiments, the electrolyte contains 1% to 60%, 10% to 60%, 20% to 50%, 20% to 40%, or 30% of propyl propionate based on the total weight of the electrolyte.
[0110] In some embodiments, examples of the additives may include, but are not limited to, one or more of fluorocarbonates, ethylene carbonate having a carbon-carbon double bond, compounds containing sulfur-oxygen double bonds, and acid anhydrides.
[0111] In some embodiments, the content of the additive is 0.01% to 15%, 0.1% to 10%, or 1% to 5%, based on the total weight of the electrolyte.
[0112] According to the embodiment of the present invention, the content of the propionate ester is 1.5 to 30 times, 1.5 to 20 times, 2 to 20 times, or 5 to 20 times that of the additive, based on the total weight of the electrolyte.
[0113] In some embodiments, the additive comprises one or more fluorocarbonates, which act together with the propionate ester to form a stable protective film on the surface of the negative electrode during charging and discharging of the lithium ion battery, thereby suppressing the decomposition reaction of the electrolyte.
[0114] In some embodiments, the fluorocarbonate has a structure of the formula C=O(OR1)(OR2), where R1 and R2 are each selected from an alkyl group or a halogenated alkyl group having 1 to 6 carbon atoms, and at least one of R1 and R2 is selected from a fluoroalkyl group having 1 to 6 carbon atoms, and optionally, R1 and R2 together with the atoms connected thereto form a 5- to 7-membered ring.
[0115] In some embodiments, examples of the fluorocarbonate may include, but are not limited to, one or more of fluoroethylene carbonate, cis 4,4-difluoroethylene carbonate, trans 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate, and ethyl trifluoroethyl carbonate.
[0116] In some embodiments, the additive comprises one or more ethylene carbonates having carbon-carbon double bonds. Examples of the ethylene carbonates having carbon-carbon double bonds may include, but are not limited to, one or more of vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, 1,2-dimethylvinylene carbonate, 1,2-diethylvinylene carbonate, fluorovinylene carbonate, trifluoromethylvinylene carbonate; vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, 1-n-propyl-2-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1,1-divinylethylene carbonate, 1,2-divinylethylene carbonate, 1,1-dimethyl-2-methyleneethylene carbonate and 1,1-diethyl-2-methyleneethylene carbonate. In some embodiments, the ethylene carbonate having a carbon-carbon double bond includes vinylene carbonate, which is easily available and can achieve better effects.
[0117] In some embodiments, the additive comprises one or more compounds containing sulfur-oxygen double bonds, examples of which may include, but are not limited to, one or more of cyclic sulfates, linear sulfates, linear sulfonates, cyclic sulfonates, linear sulfites, and cyclic sulfites.
[0118] Illustrative examples of the cyclic sulfate may include, but are not limited to, one or more of 1,2-ethylene glycol sulfate, 1,2-propanediol sulfate, 1,3-propanediol sulfate, 1,2-butanediol sulfate, 1,3-butanediol sulfate, 1,4-butanediol sulfate, 1,2-pentanediol sulfate, 1,3-pentanediol sulfate, 1,4-pentanediol sulfate, and 1,5-pentanediol sulfate.
[0119] Illustrative examples of the chain sulfate ester may include, but are not limited to, one or more of dimethyl sulfate, ethyl methyl sulfate, diethyl sulfate, and the like.
[0120] Illustrative examples of the chain sulfonate ester may include, but are not limited to, one or more of fluorosulfonate esters such as methyl fluorosulfonate and ethyl fluorosulfonate, methyl methanesulfonate, ethyl methanesulfonate, butyl dimethanesulfonate, methyl 2-(methanesulfonyloxy)propionate, and ethyl 2-(methanesulfonyloxy)propionate.
[0121] Examples of cyclic sulfonate esters include 1,3-propane sultone, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3-fluoro-1-propylene-1,3-sultone, 1-fluoro-2-propylene-1,3-sultone. The sulfuric acid may include, but is not limited to, one or more of sultone, 2-fluoro-2-propylene-1,3-sultone, 3-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone, 1,4-butane sultone, 1,5-pentane sultone, methylene methane disulfonate, ethylene methane disulfonate, and the like.
[0122] Illustrative examples of the chain sulfite ester may include, but are not limited to, one or more of dimethyl sulfite, ethyl sulfite, and diethyl sulfite.
[0123] Illustrative examples of the cyclic sulfite ester may include, but are not limited to, one or more of 1,2-ethylene glycol sulfite, 1,2-propylene glycol sulfite, 1,3-propylene glycol sulfite, 1,2-butanediol sulfite, 1,3-butanediol sulfite, 1,4-butanediol sulfite, 1,2-pentanediol sulfite, 1,3-pentanediol sulfite, 1,4-pentanediol sulfite, 1,5-pentanediol sulfite, and the like.
[0124] In some embodiments, the additive comprises one or more acid anhydrides. Examples of the acid anhydrides may include, but are not limited to, one or more of cyclic phosphoric anhydrides, carboxylic anhydrides, disulfonic anhydrides, and carboxylic acid sulfonic anhydrides. Examples of the cyclic phosphoric anhydrides may include, but are not limited to, one or more of trimethyl cyclic phosphoric anhydride, triethyl cyclic phosphoric anhydride, and tripropyl cyclic phosphoric anhydride. Examples of the carboxylic acid anhydrides may include, but are not limited to, one or more of succinic anhydride, glutaric anhydride, and maleic anhydride. Examples of the disulfonic anhydrides may include, but are not limited to, one or more of ethane disulfonic anhydride and propane disulfonic anhydride. Examples of the carboxylic acid sulfonic anhydrides may include, but are not limited to, one or more of sulfobenzoic anhydride, sulfopropionic anhydride, and sulfobutyric anhydride.
[0125] In some embodiments, the additive is a combination of a fluorocarbonate and ethylene carbonate having a carbon-carbon double bond. In some embodiments, the additive is a combination of a fluorocarbonate and a compound having a sulfur-oxygen double bond. In some embodiments, the additive is a combination of a fluorocarbonate and a compound having 2 to 4 cyano groups. In some embodiments, the additive is a combination of a fluorocarbonate and a cyclic carboxylic acid ester. In some embodiments, the additive is a combination of a fluorocarbonate and a cyclic phosphoric anhydride. In some embodiments, the additive is a combination of a fluorocarbonate and a carboxylic acid anhydride. In some embodiments, the additive is a combination of a fluorocarbonate and a sulfonic acid anhydride. In some embodiments, the additive is a combination of a fluorocarbonate and a carboxylic acid sulfonic acid anhydride.
[0126] The electrolyte is not particularly limited, and any known electrolyte may be used. In the case of a lithium secondary battery, a lithium salt is generally used.Examples of electrolytes include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, LiAlF4, LiSbF6, LiTaF6, and LiWF7; lithium tungstates such as LiWOF5; lithium carboxylates such as HCO2Li, CH3CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, and CF3CF2CF2CF2CO2Li; FSO3Li, CH3SO3Li, CH2FSO3Li, CHF2SO3Li, and CF3SO3Li. Lithium sulfonates such as CF3CF2SO3Li, CF3CF2CF2SO3Li, and CF3CF2CF2CF2SO3Li; lithium imide salts such as LiN(FCO)2, LiN(FCO)(FSO2), LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium cyclic 1,2-perfluoroethanebissulfonylimide, lithium cyclic 1,3-perfluoropropanedisulfonylimide, and LiN(CF3SO2)(C4F9SO2); LiC(FSO2)3, LiC Methylated lithium salts such as (CF3SO2)3 and LiC(C2F5SO2)3; lithium borates such as lithium bis(malonate)borate and lithium difluoro(malonate)borate; lithium phosphates such as lithium tris(malonate)phosphate, lithium difluorobis(malonate)phosphate, and lithium tetrafluoro(malonate)phosphate; and lithium phosphates such as LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2 ... The lithium salts may include, but are not limited to, fluorine-containing organic lithium salts such as iBF3CF3, LiBF3C2F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, and LiBF2(C2F5SO2)2; lithium oxalatoborate salts such as lithium difluorooxalatoborate and lithium bis(malonato)borate; lithium malonatophosphate salts such as lithium tetrafluorooxalatophosphate, lithium difluorobis(malonato)phosphate, and lithium tris(malonato)phosphate.
[0127] In some embodiments, the electrolyte is selected from LiPF6, LiSbF6, LiTaF6, FSO3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethane bissulfonylimide lithium, cyclic 1,3-perfluoropropane disulfonylimide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3, lithium difluorooxalatoborate, lithium bis(malonato)borate, or lithium difluorobis(malonato)phosphate, which contribute to improving the output power characteristics, high rate charge / discharge characteristics, high temperature storage characteristics, and cycle characteristics of the electrochemical device.
[0128] The content of the electrolyte is not particularly limited as long as it does not impair the effect of the present invention. In some embodiments, the total molar concentration of lithium in the electrolyte is more than 0.3 mol / L, more than 0.4 mol / L, or more than 0.5 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L, or less than 2.0 mol / L. In some embodiments, the total molar concentration of lithium in the electrolyte is within a range consisting of any two of the above values. When the electrolyte concentration is within the above range, the amount of lithium as a charged particle is not too small, and the viscosity can be set to an appropriate range, making it easy to ensure good electrical conductivity.
[0129] When two or more electrolytes are used, the electrolyte comprises at least one salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate. In some embodiments, the electrolyte comprises a salt selected from the group consisting of monofluorophosphate, oxalate, and fluorosulfonate. In some embodiments, the electrolyte comprises a lithium salt. In some embodiments, based on the total weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate is greater than 0.01% or greater than 0.1%. In some embodiments, based on the total weight of the electrolyte, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate is less than 20% or less than 10%. In some embodiments, the content of the salt selected from the group consisting of monofluorophosphate, borate, oxalate, and fluorosulfonate is within the range consisting of any two of the above values.
[0130] In some embodiments, the electrolyte includes one or more substances selected from the group consisting of monofluorophosphates, borates, oxalates, and fluorosulfonates, and one or more other salts. The other salts include the lithium salts exemplified above, and in some embodiments, LiPF6, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, cyclic 1,2-perfluoroethanebissulfonylimide lithium, cyclic 1,3-perfluoropropanedisulfonylimide lithium, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3, LiBF3C2F5, LiPF3(CF3)3, and LiPF3(C2F5)3. In some embodiments, the other salt is LiPF6.
[0131] In some embodiments, the content of the other salts is greater than 0.01% or greater than 0.1% based on the total weight of the electrolyte. In some embodiments, the content of the other salts is less than 20%, less than 15%, or less than 10% based on the total weight of the electrolyte. In some embodiments, the content of the other salts is within the range consisting of any two of the above values. The other salts in the above amounts contribute to the balance between the conductivity and viscosity of the electrolyte.
[0132] In addition to the solvent, additives, and electrolyte salt, the electrolyte may contain additional additives such as an anode film forming agent, a cathode protector, and an overcharge inhibitor, if necessary. The additives may be additives generally used in non-aqueous electrolyte secondary batteries, and examples thereof include, but are not limited to, ethylene carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroanisole, propane sultone, propylene sultone, and the like. These additives may be used alone or in any combination. The content of these additives in the electrolyte is not particularly limited, and may be appropriately set depending on the type of the additive, etc. In some embodiments, the content of the additive is less than 5%, in the range of 0.01% to 5%, or in the range of 0.2% to 5%, based on the total weight of the electrolyte. IV. Separator
[0133] In order to prevent short circuits, a separator is usually placed between the positive and negative electrodes, and in this case, the electrolyte of the present invention is generally used by permeating the separator.
[0134] The material and shape of the separator are not particularly limited as long as they do not impair the effects of the present invention. The separator may be a resin, glass fiber, inorganic material, etc., made of a material stable in the electrolyte solution of the present invention. In some embodiments, the separator includes a porous sheet or nonwoven fabric-like material having excellent liquid retention. Examples of resin or glass fiber separator materials include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, glass filter, etc. In some embodiments, the separator material is a glass filter. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The separator materials may be used alone or in any combination.
[0135] The separator may further be a laminate of the above materials, and may include, for example, a three-layer separator in which polypropylene, polyethylene, and polypropylene are laminated in this order, but is not limited thereto.
[0136] Illustrative examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, sulfates (e.g., barium sulfate, calcium sulfate, etc.), etc. The form of the inorganic material may include, but is not limited to, particulate or fibrous.
[0137] The separator may be in the form of a film, and may include, but is not limited to, for example, a nonwoven fabric, a woven fabric, a microporous membrane, etc. In the form of a film, the pore size of the separator is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In addition to the independent film-like separator, the following separator can be used: a separator formed by forming a composite porous layer containing the inorganic particles on the surface of the positive electrode and / or negative electrode using a resin-based binder. For example, a separator formed by forming a porous layer on both sides of a positive electrode using aluminum oxide particles with a 90% particle size of less than 1 μm using a fluororesin as a binder.
[0138] The thickness of the separator is arbitrary. In some embodiments, the thickness of the separator is more than 1 μm, more than 5 μm, or more than 8 μm. In some embodiments, the thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the separator is within a range consisting of any two of the above values. When the thickness of the separator is within the above range, it is possible to ensure insulation properties and mechanical strength, and also to ensure the rate characteristics and energy density of the electrochemical device.
[0139] When a porous material such as a porous sheet or nonwoven fabric is used as the separator, the porosity of the separator is arbitrary. In some embodiments, the porosity of the separator is more than 20%, more than 35%, or more than 45%. In some embodiments, the porosity of the separator is less than 90%, less than 85%, or less than 75%. In some embodiments, the porosity of the separator is within a range consisting of any two of the above values. When the porosity of the separator is within the above range, it is possible to ensure insulation and mechanical strength and to suppress membrane resistance, so that the electrochemical device has good rate characteristics.
[0140] The average pore size of the separator is also arbitrary. In some embodiments, the average pore size of the separator is less than 0.5 μm or less than 0.2 μm. In some embodiments, the average pore size of the separator is greater than 0.05 μm. In some embodiments, the average pore size of the separator is within the range consisting of any two of the values. If the average pore size of the separator exceeds the range, a short circuit is likely to occur. If the average pore size of the separator is within the range, a short circuit can be prevented and the membrane resistance can be suppressed, thereby providing the electrochemical device with good rate characteristics. V. Electrochemical device components
[0141] The electrochemical device member includes an electrode group, a current collecting structure, an exterior case, and a protective element. electrode group
[0142] The electrode group may have either a laminated structure in which the positive electrode and the negative electrode are laminated with the separator interposed therebetween, or a structure in which the positive electrode and the negative electrode are spirally wound with the separator interposed therebetween. In some embodiments, the mass ratio of the electrode group to the internal volume of the battery (the occupancy rate of the electrode group) is more than 40% or more than 50%. In some embodiments, the occupancy rate of the electrode group is less than 90% or less than 80%. In some embodiments, the occupancy rate of the electrode group is within a range consisting of any two of the above values. When the occupancy rate of the electrode group is within the above range, the capacity of the electrochemical device can be secured, and the deterioration of characteristics such as repeated charge / discharge performance and high-temperature storage due to an increase in internal pressure can be suppressed, and the operation of the gas release valve can be prevented. Current collection structure
[0143] The current collecting structure is not particularly limited. In some embodiments, the current collecting structure is a structure that reduces the resistance of the wiring portion and the joint portion. When the electrode group has the laminated structure, a structure in which the metal core portions of the electrode layers are bundled and welded to a terminal is applied. Since the internal resistance increases as the electrode area increases, this is also applied to the case where two or more terminals are installed in the electrode to reduce the resistance. When the electrode group has the wound structure, the internal resistance can be reduced by installing two or more lead wire structures on each of the positive electrode and the negative electrode and bundling them to the terminal. Outer case
[0144] The material of the outer case is not particularly limited as long as it is a material that is stable in the electrolyte used. The outer case may be made of metals such as nickel-plated steel, stainless steel, aluminum or aluminum alloy, magnesium alloy, or a laminated film of resin and aluminum foil, but is not limited thereto. In some embodiments, the outer case is a metal or laminated film of aluminum or aluminum alloy.
[0145] The metal exterior case may include, but is not limited to, a package sealing structure formed by welding metals together by laser welding, resistance welding, or ultrasonic welding; or a rivet joint structure formed by using the metals via a resin gasket. The exterior case using the laminated film may include, but is not limited to, a package sealing structure formed by thermally bonding resin layers together. In order to improve the sealing property, a resin different from the resin used in the laminated film can be sandwiched between the resin layers. When the resin layers are thermally bonded by the current collecting terminal to form a sealed structure, there is a bond between the metal and the resin, so that a resin having a polar group or a modified resin into which a polar group has been introduced is used as the sandwiched resin. The shape of the exterior body is also arbitrary, and may be, for example, any of a cylindrical shape, a rectangular shape, a laminated type, a button type, a pouch type, and the like. Protection Device
[0146] The protective element may be a positive temperature coefficient (PTC) element whose electrical resistance increases when abnormal heat is generated or an excessive current flows, a thermal fuse, a thermistor, a valve (current cutoff valve) that cuts off the current flowing in the circuit by suddenly increasing the internal pressure or temperature of the battery when abnormal heat is generated, etc. The protective element may be an element that does not operate under normal use of a large current, or it may be designed to prevent abnormal heat generation or thermal runaway even without a protective element. VI. Application
[0147] The electrochemical device of the present invention includes any device that generates an electrochemical reaction, and examples thereof include all kinds of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion secondary battery.
[0148] The present invention provides another electronic device comprising an electrochemical device according to the present invention.
[0149] The application of the electrochemical device of the present invention is not particularly limited, and can be used in any electronic device known in the prior art. In some embodiments, the electrochemical device of the present invention can be used in, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable fax machines, portable printers, stereo headsets, video recorders, liquid crystal televisions, portable cleaners, portable CD players, minidisks, transceivers, electronic organizers, calculators, memory cards, portable recorders, radios, backup power sources, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting equipment, toys, game consoles, watches, power tools, flashes, cameras, large-scale household storage batteries, or lithium-ion capacitors.
[0150] The following describes the preparation of lithium ion batteries with reference to specific examples, taking lithium ion batteries as an example. It should be understood that the preparation methods described in the present invention are merely exemplary, and any other suitable preparation methods are within the scope of the present invention. EXAMPLES
[0151] Examples and comparative examples of the lithium ion battery according to the present invention will be described below, and performance evaluations were carried out. 1. Making lithium-ion batteries 1. Preparation of the positive electrode
[0152] (1) Preparation of Positive Electrodes in Examples 1 to 28, Examples 35 to 39, and Comparative Examples 1 to 13
[0153] Polyvinylidene fluoride (PVDF) as a binder was added to N-methylpyrrolidone (NMP) to prepare a latex liquid (solid content 7%). After mixing was completed, lithium cobalt oxide (LCO) as a positive electrode active material was added and stirred for a predetermined time, and then graphene slurry (sheet layer graphene was uniformly dispersed in N-methylpyrrolidone with a solid content of 5% to obtain graphene slurry) was added and stirred until the system became uniform with the action of a vacuum stirrer to obtain a positive electrode slurry with a solid content of 75%. The mass ratio of each component was LCO:binder = 96:2. This positive electrode slurry was applied to 12 μm aluminum foil, dried, and cold pressed to obtain a positive electrode active material layer, which was then cut and tabs were welded to obtain a positive electrode. Based on the total weight of the positive electrode active material layer, the graphene content was W.
[0154] The positive electrodes are installed according to the conditions of the examples and comparative examples in the table below so that the positive electrodes have the corresponding configurations and parameters. (2) Preparation of Positive Electrodes in Examples 29-34 The preparation of the positive electrodes in Examples 29 to 34 was similar to that of the positive electrode in Example 5, except that the binder polyvinylidene fluoride (PVDF) and the particulate conductive agent Super P were both added to N-methylpyrrolidone to form a latex solution. 2. Preparation of the negative electrode
[0155] Artificial graphite, styrene butadiene rubber, and sodium carboxymethylcellulose were mixed with deionized water in a mass ratio of 96%:2%:2% and stirred uniformly to obtain anode slurry. This anode slurry was applied onto a 12 μm copper foil. It was then dried, cold pressed, cut, and tab-welded to obtain anode. 3. Preparation of electrolyte
[0156] Ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) (weight ratio 1:1:1) were mixed in a dry argon gas atmosphere and LiPF6 was added. 、 The mixture was mixed uniformly to form an electrolyte solution with a LiPF6 concentration of 1.15 mol / L. 4. Preparation of separator
[0157] A polyethylene (PE) porous polymer film was used as the separator. 5. Preparation of lithium-ion batteries
[0158] The resulting positive electrode, separator, and negative electrode were stacked in order, rolled up, and placed on an exterior foil, leaving an inlet for electrolyte injection. The electrolyte was injected through the inlet, and the battery was packaged and then subjected to formation, grading, and other processes to produce a lithium-ion battery. 2.Measurement method
[0159] 1. How to measure Dv10, Dv50 and Dv99 (1) Start-up of the instrument: First, turn on the sample injection system, the optical path system and the computer of the instrument, and preheat the instrument for 30 min; (2) Cleaning the sample injection system: fill the sample injector with water, adjust the rotation speed to maximum, clean for 5s, and then adjust the rotation speed to 0. Repeat the cleaning three times to ensure that the sample injector is cleaned; (3) Enter the "Manual Measurement" interface and set the material name, refractive index, material type, measurement time and measurement count in order; (4) Click "start" to collimate the light and measure the background light, and (5) The positive electrode active material was dispersed in an aqueous solution (10 mL) and measured with a laser diffraction / scattering particle size distribution analyzer (Master Sizer 3000). The sample was added to the sample pool, and the light shielding degree increased with the amount of sample added. When the light shielding degree increased to 8% to 12%, the addition of the sample was stopped, and the light shielding degree was waited until it stabilized (generally did not change after 30 s), and then "start" was clicked to start the particle size measurement. When the measurement was completed, Dv10, Dv50 and Dv99 were obtained. Each example and comparative example required measuring three parallel samples, and the average values of Dv10, Dv50 and Dv99 of the three parallel samples were calculated, and these average values were used as the Dv10, Dv50 and Dv99 values of the positive electrode active material. Dv10 means that the volume content of particles smaller than the specified particle size accounts for 10% of the total particles, Dv50 means that the volume content of particles smaller than the specified particle size accounts for 50% of the total particles, and Dv99 means that the volume content of particles smaller than the specified particle size accounts for 99% of the total particles.
[0160] 2. Measurement method of graphene (GN) sheet diameter The positive electrode was spread on a sample measuring table, and a photograph of the sample was taken with a scanning electron microscope. Using image analysis software, SEM photographs were taken at three different positions for the positive electrode in each Example or Comparative Example to obtain three SEM photographs. Ten graphenes were randomly taken from each SEM photograph, and the longest diameter of each graphene was determined as its sheet diameter using a scale. The average value of the sheet diameters of 30 graphenes in the three SEM photographs was calculated to obtain the graphene sheet diameter D1. FIG. 1 shows a scanning electron microscope (SEM) photograph of a positive electrode in Example 3 according to the present invention, and the straight lines in the figure represent the diameter of the graphene sheet. FIG. 2 is an SEM photograph of the positive electrode in Example 18 according to the present invention, which shows that graphene is present around the positive electrode active material particles.
[0161] 3. Method for measuring particle size of particulate conductive agent The positive electrode was spread on a sample measuring table, and a photograph of the sample was taken with a scanning electron microscope. SEM photographs were taken at three different positions for the positive electrode in each Example or Comparative Example to obtain three SEM photographs. Using image analysis software, 10 particulate conductive agents were randomly selected from each SEM photograph, and the area of each of these particulate conductive agents was calculated. Assuming that the particulate conductive agents were spherical, the particle diameter R (diameter) of each particulate conductive agent was calculated using the following formula. R = 2 × (S / π) 1 / 2 , where S is the area of the particulate conductive agent. The particle sizes of 30 (10×3) particles of the particulate conductive agent in the three SEM photographs were arithmetically averaged to determine the average particle size D2 of the particulate conductive agent.
[0162] 4. Sheet resistance measurement method (1) Sheet resistance was measured using a sheet resistance meter manufactured by Yuanneng Technology; (2) The power supply of the device was kept at 220 V and the air pressure was more than 0.7 MPa; (3) The positive electrode of the battery was removed when it was fully charged, and the cut positive electrode (60 × 80 mm) was placed flat on the sample mounting table; (4) After that, the sample stage was placed in the measurement chamber of the instrument and the measurement started; (5) The measurement air pressure was set to "0" throughout the entire measurement process.
[0163] 5. Method for measuring adhesive strength (1) Take a dried positive electrode and cut it into a sample with a width of 30 mm and a length of 100 to 160 mm using a blade; (2) A special double-sided tape was attached to a steel plate, with a tape width of 20 mm and a length of 90 to 150 mm; (3) The positive electrode sample cut out in step (1) was attached to double-sided tape with the measurement surface facing down; (4) A paper tape with a width equal to that of the positive electrode and a length 80 to 200 mm longer than the length of the sample was inserted under the positive electrode and fixed with a wrinkle binder; (5) Turn on the SASTEST tension machine, the indicator light will light up, and adjust the limit block to the appropriate position; (6) The sample prepared in step (4) was fixed on the measuring stage, and the paper sheet was pulled at 90° until the measurement was completed, with a speed of 10 mm / min and a measuring range of 0 to 40 mm; and (7) Save the measurement data as instructed by the software, and after the measurement was completed, remove the pole piece and turn off the device.
[0164] 6. Method for measuring brittle fracture At 25°C and 40% RH, the positive electrodes prepared in the examples and comparative examples were cold pressed to a predetermined compression density. The positive electrodes were then cut into 20mm x 100mm pole pieces, folded in half, and pressed once against the folded positive electrodes using a 2kg roller. The positive electrodes were unfolded and observed facing the lamp light. If light transmission or destruction was found in an area of 10% or more of the width, it was considered that the brittleness did not meet the processing requirements, and it was defined as serious brittle destruction. If light transmission or destruction was found in an area of 10% or less of the width, it was defined as slight brittle destruction. If no light transmission or destruction was found, it was defined as no brittle destruction. 3. Measurement results
[0165] Tables 1-1 and 1-2 show the composition, parameters, and measurement results of the positive electrodes of the examples and comparative examples. Dv50 is the DV50 of the positive electrode active material. The percentage of reduction in sheet resistance in Table 1-2 is the percentage of reduction in resistance in the examples compared to the comparative examples, which differ from the examples only in that graphene is not added.
[0166] [Table 1-1]
[0167] [Table 1-2]
[0168] As can be seen from the measurement results in Tables 1 and 2, Compared with the comparative examples, the positive electrodes in Examples 1 to 19 had significantly reduced sheet resistance (reduction >50%) and high compression density (compression >3.5 g / cc), and no or only slight brittle fracture occurred. A good conductive network distribution was formed between the graphene and the positive electrode active material, improving the electrode conduction electronic ability. In addition, by controlling the ratio Dv50 / D1 of the positive electrode active material to graphene within a predetermined range, better particle and sheet layer deposition can be achieved, improving the particle slip situation, improving the limit compression density of the positive electrode, and improving the flexibility of the positive electrode, thereby avoiding the severe brittle fracture problem in the positive electrode when highly compressed.
[0169] As can be seen from Examples 1 to 3, 9, 11 to 13 and 16 to 19, when the sheet diameter D1 of the graphene is both 10 μm, when Dv50 / D1 is between 0.45 and 4.5, the positive electrode has a sheet resistance with a drop of more than 50%, a high compression density of more than 3.5 g / cc, and no brittle fracture, compared to Comparative Example 1 in which graphene was not added. On the other hand, as can be seen from Examples 20 to 21, when Dv50 / D1<0.45, the drop in the sheet resistance of the positive electrode is <50%, and there is a serious problem of brittle fracture. First, if the sheet diameter of the graphene is too large than the particle diameter of the active material, the active material particles will aggregate with each other, the number of interfaces will increase, and there will be less graphene between the interfaces, so that the sheet resistance cannot be significantly reduced. Furthermore, since most of the active material particles do not have graphene between them and the sheet diameter is large, the graphene sheet layer cannot curve well along the gaps between the active material particles, and therefore cannot provide a slipping effect, resulting in the problem of brittle fracture at high compression densities.
[0170] As can be seen from Example 12, when Dv50 / D1 increases to 4.22, the average particle diameter D50 of the active material is large and the sheet diameter D1 of the graphene is small, so that the deposition of the positive electrode active material particles is poor, and it is difficult for the graphene to pass through the gaps between the active material particles to form a good conductive network. At the same time, the porosity of the electrode increases, affecting the transmission of ions and electrons, thereby reducing the reduction in sheet resistance. And, graphene with a small sheet diameter aggregates in the pores between the active material particles, and there is little graphene sandwiched at the particle contact interface, so there is a risk of brittle fracture due to the lack of slip action during compression.
[0171] When Dv50 / D1 is in the range of 1.0 to 3.5, the positive electrode has a significantly reduced sheet resistance (reduction of >65%) and a high compression density, and is free from the problem of brittle fracture. Furthermore, when the average particle diameter D50 of the positive electrode active material is 10 μm to 25 μm, the sheet resistance is further reduced to 0.2 to 10 ohms. As can be seen from Examples 3 to 8, the positive electrodes in Examples 3 to 4 and 6 to 7, in which the GN sheet layers are 7 to 20 layers, have better processing embrittlement than Examples 5 and 8, in which the GN sheet layers are 3 or 30 layers. This is because if the number of GN sheet layers is small, the slip action is weak, but if the number of sheet layers is too large, the flexibility is reduced, which is disadvantageous for bending the film.
[0172] In Examples 14 to 15, the amount of graphene used was increased compared to Example 3. The sheet resistance of the positive electrodes in Examples 14 to 15 was further significantly reduced, with the reduction reaching 90% or more, and the positive electrodes had a high limit compression density and were free of the problem of brittle fracture. Table 2 shows the effect of the positive electrode active material particle size Dv10 / Dv50 ratio on the positive electrode limit compression density and processing embrittlement.
[0173] [Table 2]
[0174] As can be seen from the above results, the positive electrode has high limit compression density and flexibility when Dv10 / Dv50 is between 0.33 and 0.45. On the other hand, during compression of the positive electrode, the small particle active material of an appropriate size contributes to filling the gaps of the large particle active material, thereby promoting slip between the active material particles, and further improving the limit compression density. On the other hand, some of the small particle active material fills the gaps between the large particle active material and graphene, thereby increasing the contact area between the active material and graphene, contributing to fully exerting the slip action of graphene, and further improving the flexibility of the positive electrode. Table 3 shows the effect of the particle diameter D2 of the particulate conductive agent (Super P) and the positive electrode active material Dv50 on the limit compression density and processing embrittlement of the positive electrode. The content of Super P was calculated from the total weight of the positive electrode active material layer.
[0175] [Table 3]
[0176] As can be seen from the above results, when the particle diameter D2 of the particulate conductive agent and the particle diameter Dv50 of the positive electrode active material satisfy D2 / D50<0.4 during the preparation of the positive electrode, the processing embrittlement of the positive electrode can be significantly improved. This is because graphene exists only on the surface of the active material particles, and therefore the active material particles can exhibit a slip action only when they directly contact with the particles. In contrast, the added particulate conductive agent can be dispersed in the gaps between the active material particles, so that the conductive agent particles can directly promote the slip of the active material particles that contact it during compression, thereby improving the compression density and improving the processing embrittlement. In particular, as can be seen from Examples 30 to 32, when D2 / D50=0.04 to 0.25, the positive electrode has a more significantly improved limit compression density. This is because if the conductive agent particles are too small, the filling action into the gaps is low, making it difficult to improve the compression density. On the other hand, if the conductive agent particles are too large, they fill the gaps between the active material particles, weakening their effect of promoting slippage, and the compressed density is reduced because the conductive agent particles themselves have a lower density than the active material.
[0177] Table 4 shows the effect of the ratio Dv99 / D1 of the graphene sheet diameter D1 to the positive electrode active material particle diameter Dv99 on the improvement of the positive electrode conductive performance. The rate of reduction in sheet resistance is the rate of reduction in sheet resistance in Examples 35 to 39 relative to the sheet resistance in Comparative Examples 10 to 14, respectively.
[0178] [Table 4]
[0179] As can be seen from the above results, when the relationship between the GN sheet diameter D1 and the particle diameter Dv99 of the active material satisfies Dv99 / D1=3.2-4.6, the sheet resistance of the positive electrode was reduced by more than 75%. This is because graphene exists only on the surface of the active material particles, and when the active material particles and the graphene sheet layer are in direct contact with each other, a conductive network between the particles can be constructed, and the function of conducting electrons can be achieved. Compared to the examples in which D1 / Dv99 is less than 1 / 4.6, when D1 / Dv99 is between 1 / 3.2 and 1 / 4.6, the sheet diameter of graphene is relatively large, so that it is possible to ensure that graphene extends from the deposition region of the small particle size active material. On the other hand, the specific surface area of the large particle size active material is smaller, so that it is easy to connect to the graphene on its surface and a better conductive network is constructed, and therefore the sheet resistance of the positive electrode is significantly improved.
[0180] Throughout the specification, references to "an embodiment," "partial embodiment," "one embodiment," "another example," "an example," "a specific example," or "partial example" are meant to include the particular feature, structure, material, or characteristic described in that embodiment or example in at least one embodiment or example of the invention. Thus, for example, the appearances of "in some embodiments," "in an embodiment," "in one embodiment," "in another example," "in one example," "in a particular example," or "in an example" in various places throughout the specification do not necessarily refer to the same embodiment or example of the invention. Furthermore, particular features, structures, materials, or characteristics herein may be combined in any suitable manner in one or more embodiments or examples.
[0181] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the embodiments are not to be construed as limiting the invention, and that modifications, substitutions, and alterations to the embodiments are possible without departing from the spirit, principle, and scope of the invention.
Claims
1. A positive electrode active material layer is disposed on the current collector. the positive electrode active material layer includes a positive electrode active material and graphene, A ratio Dv99 / D1 of a particle diameter Dv99 of the positive electrode active material to a sheet diameter D1 of the graphene is 3.2 to 4.
6.
2. 2. The positive electrode according to claim 1, wherein the ratio Dv10 / Dv50 of particle diameters Dv10 and Dv50 of the positive electrode active material is 0.25 to 0.
5.
3. The positive electrode according to claim 1, wherein the particle diameter Dv50 of the positive electrode active material is 0.5 μm to 35 μm.
4. The positive electrode according to claim 1, wherein the number of layers of the graphene is n, and n is 1 to 30.
5. The positive electrode according to claim 1, wherein the number of layers of the graphene is n, and n is 7 to 20.
6. The positive electrode active material layer further contains a particulate conductive agent, The positive electrode according to claim 1 , wherein a particle diameter D2 of the particulate conductive agent and a particle diameter Dv50 of the positive electrode active material satisfy D2 / Dv50<0.
4.
7. 7. The positive electrode of claim 6, wherein the particulate conductive agent comprises at least one of conductive carbon black, Super P, acetylene black, Ketjen black, and graphite.
8. 2. The positive electrode according to claim 1, wherein the positive electrode active material layer has a sheet resistance of 0.1 ohm to 550 ohm.
9. 2. The positive electrode of claim 1, wherein the positive electrode active material layer has a compressed density of 3.5 g / cc to 4.5 g / cc.
10. 2. The positive electrode of claim 1, wherein the positive electrode active material comprises at least one of a lithium transition metal composite oxide and a lithium-containing transition metal phosphate compound.
11. 10. The cathode of claim 1, wherein the cathode active material comprises at least one of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium iron phosphate.
12. 2. The positive electrode of claim 1, wherein the graphene content is 0.1 wt. % to 5 wt. %, based on a total weight of the positive electrode active material layer.
13. The coating surface density of the positive electrode active material layer is 200 mg / 1540.25 mm 2 ~330mg / 1540.25mm 2 The positive electrode according to claim 1 ,
14. An electrochemical device comprising the positive electrode according to any one of claims 1 to 13.
15. An electronic device comprising the electrochemical device of claim 14.
Citation Information
Patent Citations
Negative electrode active material, mixed negative electrode active material, and method for manufacturing negative electrode active material
JP2017199657A
Sheet-shaped positive electrode composite material for lithium ion secondary battery, manufacturing method thereof, and lithium ion secondary battery
JP2020017437A
Anode active material, anode including the anode active material, and secondary battery including the anode
JP2021501976A
Graphene dispersion, method for producing same, and electrode for secondary battery
WO2020090704A1